APOE2 eases cognitive decline during Aging: Clinical and preclinical evaluations. Issue 5 (29th March 2016) - Shinohara, Mitsuru; Kanekiyo, Takahisa; Yang, Longyu; Linthicum, Duane; Shinohara, Motoko; Fu, Yuan; Price, Laura; Frisch‐Daiello, Jessica L.; Han, Xianlin; Fryer, John D.; Bu, Guojun
Abstract : Objective: Apolipoprotein E (apoE), a major cholesterol carrier in the brain, is associated with a strong risk for Alzheimer disease. Compared to the risky APOE4 gene allele, the effects of the protective APOE 2 gene allele are vastly understudied, and thus need to be further clarified. Methods: We reviewed National Alzheimer's Coordinating Center clinical records and performed preclinical experiments using human apoE‐targeted replacement (apoE‐TR) mice, which do not show amyloid pathology. Results: Clinically, the APOE2 allele was associated with less cognitive decline during aging. This effect was also seen in subjects with little amyloid pathology, or after adjusting for Alzheimer disease‐related pathologies. In animal studies, aged apoE2‐TR mice also exhibited preserved memory function in water maze tests. Regardless, apoE2‐TR mice showed similar or greater age‐related changes in synaptic loss, neuroinflammation, and oxidative stress compared to apoE3‐TR or apoE4‐TR mice. Interestingly, apoE concentrations in the cortex, hippocampus, plasma, and cerebrospinal fluid (CSF) were positively correlated with memory performance across apoE isoforms, where apoE2‐TR mice had higher apoE levels. Moreover, apoE2‐TR mice exhibited the lowest levels of cholesterol in the cortex, despite higher levels in CSF and plasma. These cholesterol levels were associated with apoE levels and memory performance across apoE isoforms. Interpretation: APOE2 is associated with less cognitive decline during aging. This can occur independently of age‐related synaptic/neuroinflammatory changes and amyloid accumulation. Higher levels of apoE and associated cholesterol metabolism in APOE2 carriers might contribute to this protective effect. Ann Neurol 2016;79:758–774